EFFECTS COMMUNICATION FLASH CARDS ON KNOWLEDGE AND ATTITUDE RELATED TO WOMEN'S CLASSICAL CANCER IN REPRODUCTIVE AGE IN NUSA INDAH PUSKESMAS AREA, BENGKULU CITY IN 2023 - Rolita Efriani; Inne Delia A; Eliana Eliana; Epti Yorita; Rialike Burhan (Poltekkes Kemenkes Bengkulu, 2023)
The coverage of cervical early detection by clinical examination in the working area of ??Bengkulu city medical center in 2019 of the total number of women of childbearing age was 50,240, only 3,833 (7.6%) Perform cervical and breast exams. Similarly, in 2020, out of 62,160 women of reproductive age, only 1,967 (3.2%) were tested, and for the 2021 aggregate, out of 62,160 women of reproductive age, 5,901 (9.5%) is detected early. cancer through IVA and SADANIS (Bengkulu City Health Office, 2021). This study aimed to determine the effectiveness of flashcards on knowledge and attitudes towards cervical cancer among older adults at the Nusa Indah Public Health Center work area, City from Bengkulu in 2023. Study design using Quassy experimental design research methodology. Know the increase in knowledge and attitude achieved through pre- and post-test activities. In this study, the experimental group was divided into 2 (two) groups, one group was advised by flashcards, the other group received leaflets. The research instrument used in this study was a questionnaire. Research results from data analysis show that there is a significant difference between knowledge and attitude scores before and after the intervention, the p value obtained is 0.000 (<0.05). Wilcoxon test results show that there is a difference in mean knowledge and attitude scores before and after the intervention using flashcards and leaflets with a P value of 0.000 (0.05), meaning there is a effective in implementing interventions with flashcards and leafleat.